2005
DOI: 10.1111/j.1444-2906.2005.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific thermal denaturation pattern of fish myosin when heated as myofibrils as studied by myosin subfragment-1 and rod denaturation rates

Abstract: Thermal denaturation of myofibrils from various species of fish was investigated by measuring ATPase inactivation, myosin aggregation, myosin subfragment-1 (S-1) and rod denaturation rates as studied by chymotryptic digestion. Decrease in monomeric myosin (myosin aggregation) was always faster than the ATPase inactivation for all myofibrils tested. The relative denaturation rate of rod to that of S-1 differed from species to species. Preceded denaturation of rod was observed with some species, and the opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Moreover, slow decrease of rod production found with tilapia myofibrils was accompanied by the generation of aggregates. It is reported that S-1 and rod denaturation profile was fish-species specific [4]. The above conclusion including ours was led based on the heating experiments in 0.1 M NaCl, pH 7.5.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Moreover, slow decrease of rod production found with tilapia myofibrils was accompanied by the generation of aggregates. It is reported that S-1 and rod denaturation profile was fish-species specific [4]. The above conclusion including ours was led based on the heating experiments in 0.1 M NaCl, pH 7.5.…”
mentioning
confidence: 95%
“…S-1 and rod denaturation pattern was dependent on the pH for heating. It has been proposed 15 that S-1 and rod denaturation pattern is fish species-specific [4], which was concluded from the experimental results conducted at pH 7.5. We added a modified proposal that S-1 and rod denaturation pattern is also affected by the factors that affects myosin filament structure, pH in this paper.…”
mentioning
confidence: 96%
See 3 more Smart Citations